Radiolabeled Peptides for Molecular Imaging of Apoptosis - Mosayebnia, Mona; Hajiramezanali, Maliheh; Shahhosseini, Soraya (Current Medicinal Chemistry, 2020)
Apoptosis is a regulated cell death induced by extrinsic and intrinsic stimulants. Tracking of apoptosis provides an opportunity for the assessment of cardiovascular and neurodegenerative diseases as well as monitoring of cancer therapy at early stages. There are some key mediators in apoptosis cascade, which could be considered as specific targets for delivering imaging or therapeutic agents. The targeted radioisotope-based imaging agents are able to sensitively detect the physiological signal pathways which make them suitable for apoptosis imaging at a single-cell level. Radiopeptides take advantage of both the high sensitivity of nuclear imaging modalities and favorable features of peptide scaffolds. The aim of this study is to review the characteristics of those radiopeptides targeting apoptosis with different mechanisms.
Keywords: Single Photon Emission Computed Tomography (SPECT)